Development Of Omnidirectional Drive System Using Mecanum Wheels For Patient Transfer Device - Mokhtar, Mohamad Dzul Asyraf (Universiti Sains Malaysia, 2022)
Work-related musculoskeletal disorders (WMSD), especially lower back pain is reported as one of the main health problems among healthcare workers. The causes of the problem are mainly healthcare tasks such as manual patient handling and moving beds. There are several solutions that are already available in the market, proven to be able to solve the problem. However, there are currently no device in the market that is equipped with omnidirectional movement capability, which strictly limits the mobility of the device in cramped space, and also complicating the controls. In this project, a Mecanum wheel drive system is created and integrated onto a patient transfer device to allows omnidirectional movement. The completed prototype’s performance is verified by comparing it with a MATLAB simulation. The result shows that the prototype is able to move in the same motion as simulated with some deviation. The largest deviation measured is during leftward movement with deviation of 11.5cm on the left wheel and 11.8cm on the right wheel. However, even with the deviation, the prototype successfully completed a patient transfer process